Capsule networks for 3D pose estimation in computer graphics - Picos, Kenia; Orozco Rosas, Ulises; Cuesta-Infante, Alfredo; Sanz, Antonio; Pantrigo, Juan José (My University, 2020)
Pose estimation is an important task for novel engineering applications, such as virtual and augmented reality (VR/AR), pose-based video games, object reconstruction, target tracking, driving assistance and recent sports analytics. Commonly, an efficient pose estimation system depends on the pose visualization given by a 3D configuration of location, orientation, and scaling parameters of the target. In this work we implement Capsule Networks to solve 3D pose estimation in computer graphics of rigid objects using a multi-GPU architecture
Keywords: Capsule networks; 3D pose estimation; Campus Tijuana